The perpetrator in focus: Turn of the century Holocaust remembrance in The Specialist - F. Guerin (Law Text Culture, 2006)
In his controversial 1998 film, The Specialist, Israeli director Eyal Sivan casts the Holocaust in a new light when he represents it through the eyes of the Nazi perpetrator. Sivan and his scriptwriter, human rights activist Rony Brauman, re-assemble and manipulate footage originally filmed by Leo Hurwitz for Capital Cities Broadcasting of Adolf Eichmann’s trial by an Israeli court in Jerusalem in 1961. Specifically, Sivan recycles the video footage of the trial into a 16mm film that critiques, not the heinous nature of Eichmann’s crimes, nor the depravity of the man who committed them, but the system of regulation that constructed and judged Eichmann. While the video footage was originally filmed as a document of the trial, Sivan radically redeploys the same images in a narrative that exposes the manipulations of the court, its representations and the continued injustice of such institutions and representations today, 45 years later. According to The Specialist, Eichmann’s actions are not on trial; they are a foregone conclusion. To prove Eichmann’s guilt or innocence was not the point of the trial in the first place, and it is certainly not the goal of The Specialist. Through its careful weaving of fragments of the proceedings, over the course of its narrative, The Specialist reveals the relationship of otherness — the differences and identicalities — between Adolf Eichmann, the ‘deportation specialist’ and Attorney General Gideon Hausner for the prosecution. Simultaneously, the film considers the relationship between Eichmann and the crimes of the National Socialist Party as they were forged by the Israeli court.